From Café to Content: Hanging Out as a Symbolic Practice of Digital Identity Construction among Urban Youth - Hemarida Nabilah Putri Rida; Kanaya Aulia Ahmad Kanaya (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
This study aims to examine how urban youth construct the meaning of hanging out as part of contemporary lifestyles. Using a qualitative approach and a case study strategy, the research was conducted at a café in South Tangerang, involving six purposively selected informants. Data were collected through in-depth interviews, observation, and documentation, and analyzed using a symbolic interactionist perspective. The findings reveal that hanging out is not merely a recreational activity, but a multidimensional social practice encompassing social interaction, emotional regulation, symbolic consumption, and digital identity production. Hanging out serves as a space where adolescents build relationships, express themselves, and negotiate their identities, both through face-to-face interaction and social media engagement. These findings highlight that seemingly mundane everyday practices embody complex social meanings in the lives of urban youth. This study contributes to the sociology of youth and lifestyle studies by providing a deeper understanding of the relationship between social space, interaction, and meaning making in the digital era.